Improving The Methodology of Managing Construction Materials Manufacturing Enterprises - Achilov Ilmurad Nematovich (Academia Open, 2026)
General Background: The construction materials manufacturing industry plays a decisive role in national economic development, infrastructure modernization, and housing provision, requiring efficient enterprise management systems to meet growing demand while optimizing costs and ensuring quality. Specific Background: Construction materials enterprises face specific challenges including production process continuity, high energy and raw material intensity, significant logistics costs, and complex technological processes, yet management systems remain predominantly reactive with insufficient strategic planning and weak integration between strategic and operational levels. Knowledge Gap: Despite extensive international literature on strategic management tools (Porter's competitive advantage, Balanced Scorecard, Lean, Theory of Constraints, ISO 9001) and domestic studies highlighting sectoral problems in Uzbekistan, a comprehensive integrated methodology systematically linking strategy, KPIs, process-based management, supply chain optimization, and quality systems adapted to construction materials manufacturing specifics remains underdeveloped. Aims: This study examines improving the management system methodology of construction materials manufacturing enterprises through scientific-theoretical and practical perspectives, analyzing production dynamics, import dependency, and growth stability using economic-mathematical methods. Results: Analysis of Uzbekistan's cement sector (2020-2024) revealed unstable growth patterns (CAGR 6.2%, coefficient of variation 14.32%, instability index 18.10%) with sharp fluctuations indicating reactive decision-making, energy supply disruptions, and insufficient supply chain coordination despite declining import dependency from 16.6% to 8.6%. Novelty: The research scientifically substantiates integrating KPIs/Balanced Scorecard, Theory of Constraints, Lean approaches, and ISO 9001 quality management within a unified comprehensive management methodology specifically adapted to construction materials sector characteristics. Implications: The proposed comprehensive approach provides a scientific foundation for modernizing management practices, enhancing resource efficiency, ensuring production sustainability, and strengthening competitiveness through systematic linkage of strategic objectives with operational execution and digital technology integration.Keywords : Construction Materials Management, Enterprise Performance Optimization, Strategic KPI Systems, Lean TOC Integration, Production Stability AnalysisHighlight : Production volatility reveals reactive decision-making rather than strategic planning and forecasting mechanisms. Integration of KPIs, Balanced Scorecard, Lean, and Theory of Constraints creates comprehensive methodology. Import dependency declined from 16.6% to 8.6% between 2020 and 2024.